Knowing Johannesburg otherwise: exploring Black feminist space in conversation with Senzeni Marasela and Katherine McKittrick - Vosloo, Jana Lydia (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.